2009
DOI: 10.3184/030823409x393664
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-promoted cleavage of the C-17-dihydroxyacetone side chain of corticosteroids in aqueous ammonia water

Abstract: A convenient approach to 17-ketosteroids by the iodine-promoted cleavage of the C-17-dihydroxy acetone side chain of corticosteroids is described. Treatment of steroids containing the C-17-dihydroxyacetone side chain with iodine and an excess of aqueous ammonia in acetonitrile at 50°C, affords high yields of the corresponding 17-ketosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A quite recent report showed that Bi(OTf) 3 ·xH 2 O is an efficient catalyst for the conversion of corticosteroids into highly functionalized 17-ketosteroids, by cleavage of the C17-dihydroxyacetone side chain [ 99 ]. This reaction was typically performed using large amounts of oxidative or basic reactants [ 100 , 101 , 102 ]. The use of other bismuth(III) salts and other solvents has been tested, however the best results have been obtained with 0.05 eq.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…A quite recent report showed that Bi(OTf) 3 ·xH 2 O is an efficient catalyst for the conversion of corticosteroids into highly functionalized 17-ketosteroids, by cleavage of the C17-dihydroxyacetone side chain [ 99 ]. This reaction was typically performed using large amounts of oxidative or basic reactants [ 100 , 101 , 102 ]. The use of other bismuth(III) salts and other solvents has been tested, however the best results have been obtained with 0.05 eq.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“… [7] Removal of the C17 side chain of corticosteroids has traditionally involved the use of excess amounts of strong oxidizing agents such as NaBiO 3 , [8] NaBH 4 /NaIO 4 , [9] CrO 3 [10] or MnO 2 [11] . Additional methods involving excess I 2 /NH 3 [12] and strong bases [13] have also been developed, although with either moderate yields or limited applicability. More recently, cleavage of hydroxyacetone side chains with bismuth(III) catalysts has been reported [14] .…”
Section: Introductionmentioning
confidence: 99%
“…[7] Removal of the C17 side chain of corticosteroids has traditionallyi nvolved the use of excess amounts of strong oxidizing agents such as NaBiO 3 , [8] NaBH 4 /NaIO 4 , [9] CrO 3 [10] or MnO 2 . [11] Additional methods involving excessI 2 /NH 3 [12] and strong bases [13] have also been developed,a lthough with either moderatey ields or limited applicability.M ore recently,c leavageo fh ydroxyacetone side chains with bismuth(III) catalysts has been reported. [14] Due to the shortcomings of these methods and the difficulties associated with the selective side chain removal without degradation of the androstane skeleton, microbial approaches from phytoster-ols have been intensely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Later, an optimized procedure that uses 5.0 equiv of sodium methoxide in refluxing 1,4-dioxane has been described . More recently, the direct conversion of corticosteroids into 17-ketosteroids by using iodine in the presence of an excess of aqueous ammonia has also been reported …”
mentioning
confidence: 99%